Modern contractualism and political guilt - Herrera Romero, Wilson Ricardo (Estudios de Filosofía, 2010)
This article analyzes the problem of how to deal with situations in which our moral beliefs run contrary to the demands of a Government which counts on the decided support of the majority of members of the political community to which one belongs. Following the thesis set by Jaspers in The Problem of Guilt, we will try to show that if the concept of Political Guilt proposed by Jaspers is interpreted in the line of the liberal philosopher John Locke, new light can be cast on what Political Responsibility means. This will also enable us to show that the so-called Political Obligations of citizens extend beyond the institutional requirements, a theme which has recently been the focus of discussion among those scholars that deal with the question of Political Legitimacy from the perspective of modern Contractualism. The said extension consists basically in that the citizens have Political Obligations related to the Political Culture that constitute their Political Identity